SPEECH ACT AND POLITENESS IN SUNDANESE LANGUAGE - Aip Syaepul Uyun (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2022)
The aims of this study is to describe on how politeness occurred in Sundanese language, and what makes Sundanese politeness differed from any other languages. The research used qualitative methode and the data was collected through interview, and document analysis.  It was conducted to collect the data about Sundanese people perception toward the Sundanese language, and also their believe on the Sundanese politeness in its language. The findings showed the fact that Sundanese people do not all speak politely, since the geographical place and acculturation plays significant roles on its existence. As the result, the Sundanese politeness appeared according to the background of the region which affects the language. Meanwhile, language structure, lexical variable usage and also the manner of Sundanese people communicate is fundamental variable indicating politeness in speech act in Sundanese language.